Verbundforschung und die Zukunft der Mediävistik - Drews, Wolfram; Grünbart, Michael; Oschema, Klaus (Das Mittelalter, 2021)
In general, scholarly monographs written by a single author still seem to be the most common form for publishing research results. This holds true especially for the doctoral thesis, but also for the Habilitation, still common in German-speaking academia. However, collaborative research is no new trend taken over from the natural sciences. There is a long tradition of collaborative research both in Germany (reaching back to the 19th century), and in France, going back even to the 18th century. In the 20th century, the German Research Foundation (DFG) initiated several research formats meant to foster interdisciplinary research. Medieval studies have been involved in such projects almost from the start. At present, such projects are either based at individual universities, or they involve scholars from different institutions. For specialists from disciplines with few permanent positions, this can be an excellent opportunity to document the usefulness of their subjects to broader research initiatives. This has turned out to be a key element in securing the future of so-called smaller disciplines, which can show their importance by providing chronological or methodological links between other subjects. Recent trends, such as the study of the Global Middle Ages, have highlighted the necessity for scholars of various disciplines to join their efforts to produce results that would never have been achieved without interdisciplinary and transdisciplinary cooperation. However, some drawbacks should not be overlooked: The increasing number of research projects has led to a significant rise in the number of highly qualified researchers, who find it increasingly difficult to secure permanent positions at universities matching their experience.